The Properties of a New Subclass of Harmonic Univalent Mappings - Zhi-Hong Liu; Ying-Chun Li (Abstract and Applied Analysis)
We introduced a new subclass of univalent harmonic functions defined by the shear construction in the present paper. First, we showed that the convolutions of two special subclass harmonic mappings are convex in the horizontal direction. Secondly, we proved a necessary and sufficient condition for the above subclass of harmonic mappings to be convex in the horizontal direction. We also presented some basic examples of univalent harmonic functions explaining the behavior of the image domains.